On the beta function and the neutrix product of distributions - Fisher, Brian; Kilicman, Adem; Nicholas, Joel D. (Overseas Publishers Association, 1998)
The Beta function B(x,n) and the related Beta functions B(x ±, n) and B±(x,n) are defined as distributions and a number of neutrix products of distributions are evaluated.